Proximate Composition and Chemical Profiles of Reishi Mushroom (Ganoderma lucidum (Curt: Fr.) Karst) - Garuba, T.; Olahan, G. S.; Lateef, A. A.; Alaya, R. O.; Awolowo, M.; Sulyman, A. (Journal of Scientific Research, 2020)
Ganoderma lucidum is a mushroom commonly used in folk medicine especially Traditional Chinese Medicine (TCM) but information on its nutritional and chemical profiles remains insufficient. This work aimed at evaluating proximate composition and identification of bioactive compounds in ethanolic extract of G. lucidum. Pulverized G. lucidum was suspended in ethanol in 1:10 and extraction was carried out by rotary evaporation to produce G. lucidum extract (GLE). Proximate composition of the sample was analyzed. Fourier Transform Infrared (FTIR) spectroscopy was carried out to identify different functional groups in GLE. Gas Chromatography-Mass Spectrometry (GC-MS) was used to determine the bioactive compounds of the sample. Proximate analysis revealed that the amount of carbohydrate in sample was the highest (44.95%), followed by protein (15.75%). FTIR results showed that OH, C=O, C-OH, N-H 1* and 2* and alkyl halide are functional groups in GLE. A total of twelve (12) bioactive compounds were identified and the most prevailing compound in GLE was ethyl octadeca-9,12-dienoate (45.95%), followed by ethylhexadecanoate / ethyl palmitate (18.09%). Guaiacol (4.95%), octadecanoic acid (5.37%), ethylcyclohexane (3.31%) were also present. It can be inferred from this study that G. lucidum is nutritional and contains bioactive compounds that are useful in nutraceutical and pharmaceutical industries.